Equitable Claims and Future Considerations: Road Building and Colonization in Early Ontario, 1850–1890 - Murray, Derek (Journal of the Canadian Historical Association / Revue de la Société historique du Canada)

(untitled) (The Canadian Historical Association / La Société historique du Canada, 2013)
In the 1850s, the government of Canada West initiated a project to colonize a vast “waste land” known as the Ottawa-Huron Tract. Resettlement was encouraged through the building of a network of colonization roads and the offer of free grant lots along the roads. In the backwoods, where topography defied the logic of the grid, the placement and maintenance of roads was crucial, not only for convenience, but for survival. Analysing the process whereby settlers and the state negotiated road construction projects, this article reveals an emerging local democratic culture in which frustration with bureaucracy often meant more to community formation than did social status, religion, or ethnicity. In a series of letters and petitions sent to the colonization roads administration from 1863 to 1888, residents of Brudenell, Ontario, articulated a vision of resettlement in which the state played a supporting rather than determining role. While much has been written about the failure of intensive commercial agriculture on the Precambrian Shield, settlers succeeded in building communities and, sometimes, in channelling government resources toward local initiatives.